Indeks Keterpaparan Banjir dan Banjir Pasang di Kota dan Kabupaten Pekalongan - Halimatus Sa’diyah; Imam Buchori; Amirudin Amirudin (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Sa’diyah H, Buchori I, Amirudin A. 2020. Exposure index of flood and tidal flood in the city and regency of Pekalongan. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Climate change can increase the threat of disasters, such as floods, prolonged drought, tidal waves, and others. Pekalongan City is one of the areas vulnerable to the impacts of climate change, especially in the form of floods and tidal floods. Exposure is the degree, duration and/or extent of the impact of a system or subject's contact with the disturbance. This study used a spatial model of the exposure index method. Data obtained from primary data (questionnaire surveys, field observations, and geospatial data analysis) and secondary data (statistical data from city and district governments and sub-district / village offices). The results of the exposure index modeling are classified into five classes with very high, high, medium, low, and very low. The purpose of this study is to analyze the spatial model of exposure index in the coastal areas of the city and regency of Pekalongan and the areas included in the Kupang River Basin. This study produces the distribution of the exposure index in the city and regency of Pekalongan which shows that the exposure index is dominated by high categories with a proportion value of 49%.